A Comprehensive Clinical Study on Bhringaraja (Eclipta alba Hassk) Churna for the Treatment of Ekakusta (Psoriasis) - T. Srinivas; S.Babu rao; A.Vijaya lakshmi (AYUSHDHARA, 2025)
Objectives: This study was conducted to evaluate the efficacy of Bhringaraja (Eclipta alba Hassk) Churna in the management of Ekakusta (psoriasis). Materials and Methods: A single arm randomized open clinical study was conducted at Govt. Ayurvedic Hospital, Erragadda, Hyderabad. A total of 30 patients were selected and treated with 3 grams of whole plant powder of Bhringaraja (Eclipta alba) administered orally twice a day, 30 minutes before meals, along with lukewarm water. Additionally, the whole plant powder was used once a day as a Pradeha (application) with lukewarm water, as required, for 4 hours. The treatment was continued for 45 days, with results being assessed and recorded every 15 days. Subjective and objective parameters were analyzed before and after the treatment. In subjective parameters Aswedhanam and Matsyasakalopanam are taken while PASI Score as objective parameter. Results: It was observed that in subjective parameters 17% were in mild relief, 73% were of moderate relief and there was good relief in 10% of patients. In objective parameter 10% were in mild relief, 73% were of moderate relief and there was good relief in 17% of patients. Both subjective and objective parameters have been analyzed statistically. The relief of Aswedhanam and Matsyasakalopanam found highly significant (P<0.001) and same results in reduction of PASI score also. Conclusion: The conclusion of the present study, which aimed to evaluate the therapeutic efficacy of Bhringaraja (Eclipta alba Hassk) whole plant powder administered both internally and externally in managing Ekakusta (psoriasis), indicates promising results. The clinical trial demonstrated significant improvements in the patients’ symptoms, including Aswedhanam (loss of sweating) and Matsyasakalopanam (scaling), as evidenced by a marked reduction in the Psoriasis Area and Severity Index (PASI) scores. These findings suggest that Bhringaraja whole plant powder may be an effective treatment modality for alleviating the signs and symptoms of psoriasis.